Correction of the ultrastructural changes of the respiratory department of the lungs by phosphatidylcholine liposomes due to multiple skeletal trauma with osteosynthesis in the experimental study - L. M. Zaiats; U. V. Kuz; W. Zukow (Kazimierz Wielki University, 2018)
It was made the experimental study on white male rats by an electron microscopic method in dynamics (6, 24, 72, 168 h) and was studied the possibility of correction of ultrastructural changes of the respiratory department of the lung by phosphatidylcholine liposomes ("Lipin" medium) due to multiple skeletal trauma with the use of intramedullary osteosynthesis. It is defined that intraperitoneal Lipin administration in dose 50 mg/kg body weight during the first 24 hours after beginning of the study case decrease the expressiveness and prevalence of damage alveolar cells І and ІІ type, haemocapilari endothelial cells and alveolar macrophages. The Lipin administration does not influence on the character of ultrastructural changes of the respiratory department of the lung while increasing time of the experiment (72-168 hours).